2020
DOI: 10.1002/cam4.2822
|View full text |Cite
|
Sign up to set email alerts
|

LINC‐PINT alleviates lung cancer progression via sponging miR‐543 and inducing PTEN

Abstract: Long intergenic nonprotein coding RNA p53‐induced transcript (LINC‐PINT) has been reported to participate in various cancers. Here, we investigated the effects of LINC‐PINT on lung cancer progression. Firstly, in our study, we implied that LINC‐PINT was obviously decreased in NSCLC. Thereafter, in A549 and H1299 cells, LINC‐PINT was upregulated via transfecting LV‐LINC‐PINT. As exhibited, LINC‐PINT repressed cell proliferation and cell colony formation of A549 and H1299 cells. Subsequently, flow cytometry evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…13 For example, LINC-PINT weakens the growth and colony formation of A549 and H1299, and inhibits the migration and invasion of NSCLC cells by regulating different genes. 14,15 On the other side, studies have also suggested that lncRNAs aggravate NSCLC progression. For instance, Ye et al found that lncRNA-BLACAT1 accelerates the growth, migration and metastasis of NSCLC by sponging miR-144.…”
Section: Discussionmentioning
confidence: 99%
“…13 For example, LINC-PINT weakens the growth and colony formation of A549 and H1299, and inhibits the migration and invasion of NSCLC cells by regulating different genes. 14,15 On the other side, studies have also suggested that lncRNAs aggravate NSCLC progression. For instance, Ye et al found that lncRNA-BLACAT1 accelerates the growth, migration and metastasis of NSCLC by sponging miR-144.…”
Section: Discussionmentioning
confidence: 99%
“…18 LINC-PINT inhibits lung cancer cell growth, cell cycle, migration and invasion while promoting apoptosis. 19 In addition, lncRNA MIAT upregulation leads to accelerated cell growth and predicts poor prognosis in lung cancer. 14 There are still a lot of lncRNAs whose functions are unclear in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, qRT-PCR results displayed that miR-543 expression in NSCLC tissues and their cell lines was significantly up-regulated ( Figure 3D and E), which was consistent with previous report. 16 In addition, it was observed that GATA6-AS1 overexpression could down-regulate miR-543 expression in H1299 cells, while knocking down GATA6-AS1 could lead to opposite result in H460 cells ( Figure 3F). These results suggested that GATA6-AS1 targeted miR-543 to negatively regulate its expression.…”
Section: Gata6-as1 Targeted Mir-543mentioning
confidence: 90%
“…15 A previous study reports that miR-543 is highly expressed in NSCLC and exerts tumor-promoting effects via repressing PTEN. 16 However, the mechanism of abnormal expression of miR-543 in NSCLC is not clear.…”
Section: Introductionmentioning
confidence: 99%